2023
DOI: 10.3390/antiox12030673
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Model for Parkinson’s Disease Based on Transcriptional Gene Activation via KEAP1/NRF2 to Develop New Antioxidant Therapies

Abstract: Investigations of the effect of antioxidants on idiopathic Parkinson’s disease have been unsuccessful because the preclinical models used to propose these clinical studies do not accurately represent the neurodegenerative process of the disease. Treatment with certain exogenous neurotoxins induces massive and extremely rapid degeneration; for example, MPTP causes severe Parkinsonism in just three days, while the degenerative process of idiopathic Parkinson´s disease proceeds over many years. The endogenous neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…As mentioned, α-Syn is an unfolded protein that accumulates in Lewy bodies, a hallmark of PD [ 111 ]. Aminochrome, on the other hand, is an endogenous DA neurotoxin [ 11 ]. Compared to microglia, astrocytes are not well equipped with receptors that can recognize pathogens.…”
Section: Astrogliamentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, α-Syn is an unfolded protein that accumulates in Lewy bodies, a hallmark of PD [ 111 ]. Aminochrome, on the other hand, is an endogenous DA neurotoxin [ 11 ]. Compared to microglia, astrocytes are not well equipped with receptors that can recognize pathogens.…”
Section: Astrogliamentioning
confidence: 99%
“…On the other hand, recessive DNAJC6 mutations can present as atypical Parkinsonism [ 7 ]. Additionally, the potential contribution of environmental toxins, such as herbicides (e.g., paraquat), insecticides (e.g., rotenone), an excess accumulation of iron or manganese [ 3 , 8 , 9 , 10 ], as well as exposure to endogenous toxins such as salsolinol or aminochrome, to PD pathology was verified [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is a novel mode of iron-dependent cell death induced by lipid peroxidation, which is distinguished from apoptosis, necrosis, pyroptosis and autophagy, and is mainly characterised by iron accumulation and lipid peroxidation. 5 Numerous studies have found that ferroptosis is involved in a variety of diseases including neurodegeneration, 6 stroke, 7 cerebral haemorrhage, 8 and AKI 9 and that targeting the activation or inhibition of the pathways corresponding to ferroptosis can intervene in the onset and progression of disease. It was found that iron overload induced ferroptosis in renal tubular epithelial cells and was involved in the development of AKI.…”
Section: Introductionmentioning
confidence: 99%
“…These articles aim to review the recent findings in the ND field and highlight the gaps in knowledge and future research directions. The reviews cover important directions such as (i) the identification of new potential biomarkers for age-related ND disease progression that can be modulated for therapeutic purposes [ 10 ]; (ii) the development of a new preclinical model for PD to test new potential drugs, with an increased potential to limit disease progression or cure it [ 11 ]; (iii) the role of nutraceuticals and physical exercise in controlling oxidative balance and improving functional outcomes in NDs [ 12 , 13 ]; (iv) mitochondrial function and oxidative stress in relation to successful cellular therapy for stroke [ 14 ].…”
mentioning
confidence: 99%
“…Juan Segura-Aguilar and his colleagues studied a KEAP1/NRF2 transcriptional activation preclinical model for PD, because no current treatments for PD are guaranteed to work, and no one has studied the effect of antioxidants on idiopathic PD [ 11 ]. This model will be useful for the development of new potential antioxidant therapies [ 11 ].…”
mentioning
confidence: 99%